COVID-19 among Black people in Canada: a scoping review - Olanlesi-Aliu, Adedoyin; Kemei, Janet; Alaazi, Dominic; Tunde-Byass, Modupe; Renzaho, Andre; Sekyi-Out, Ato; Mullings, Delores V.; Osei-Tutu, Kannin; Salami, Bukola (My University, 2024)
The COVID-19 pandemic exacerbated health inequities worldwide. Research conducted in Canada shows that Black populations were disproportionately exposed to COVID-19 and more likely than other ethnoracial groups to be infected and hospitalized. This scoping review sought to map out the nature and extent of current research on COVID-19 among Black people in Canada. Following a five-stage methodological framework for conducting scoping reviews, studies exploring the effects of the COVID-19 pandemic on Black people in Canada, published up to May 2023, were retrieved through a systematic search of seven databases. Of 457 identified records, 124 duplicates and 279 additional records were excluded after title and abstract screening. Of the remaining 54 articles, 39 were excluded after full-text screening; 2 articles were manually picked from the reference lists of the included articles. In total, 17 articles were included in this review.
Keywords: racialized populations; inequity; vaccine hesitancy; racial discrimination